2018
DOI: 10.1136/bmjopen-2018-022612
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors at work and inflammatory markers: protocol for a systematic review and meta-analysis

Abstract: IntroductionChronic inflammation may be a mediator for the development of cardiovascular disease (CVD), metabolic diseases and psychotic and neurodegenerative disorders. Meta-analytic associations between work-related psychosocial factors and inflammatory markers have shown that work-related psychosocial factors could affect the flexibility and balance of the immune system. However, few systematic reviews or meta-analyses have investigated the association between work-related psychosocial factors and inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Multiple lines of evidence suggest that high job stress is associated with increased levels of inflammatory markers such as CRP, IL-6, and TNF-α 25 , 29 ) . Such evidence supports that alleviating job stress may lead to a reduction in basal level of inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple lines of evidence suggest that high job stress is associated with increased levels of inflammatory markers such as CRP, IL-6, and TNF-α 25 , 29 ) . Such evidence supports that alleviating job stress may lead to a reduction in basal level of inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies indicated that chronic psychosocial job stress elevates inflammatory markers such as C-reactive protein (CRP), interleukin (IL)-6, and tumor necrosis factor (TNF)-α 22 , 23 , 25 , 26 , 27 , 28 , 29 ) . These studies observed that workers with higher job stress (low organizational justice, increased job strain, or low social support) exhibited increased levels of CRP and IL-6 22 , 23 , 26 ) compared to the lower stress counterpart.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of the limitations of previous and current research attempts [30][31][32], our investigation aims at advancing knowledge on the association of working conditions and systemic inflammation among employees particularly by three contributions: (1) We will only incorporate prospective studies to draw our effect estimates upon on a study base with high level of evidence designs. (2) A criteria-based classification of working conditions based on prominent job stress models will be provided, and digital technology use will be considered as a particular type of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a paucity of reviews and meta-analyses examining systemic inflammatory processes due to working conditions and/or workrelated stress. Previous reviews and meta-analyses have focused on associations between workplace stress and immune function [30,31], and on work-related psychosocial factors and inflammatory markers [32]. However, to our knowledge, there are no systematic reviews and metaanalyses investigating the strength of the evidence on the prospective association of various modern working conditions including digital technology use and employees' systemic inflammatory markers.…”
Section: Introductionmentioning
confidence: 99%